The relationship between inflammatory state and quantity of affective episodes in bipolar disorder. (April 2018) - Queissner, Robert; Pilz, René; Dalkner, Nina; Birner, Armin; Bengesser, Susanne A.; Platzer, Martina; Fellendorf, Frederike T.; Kainzbauer, Nora; Herzog-Eberhard, Simone; Hamm, Carlo; Reininghaus, Bernd; Zelzer, Sieglinde; et al.
Highlights: We conducted a study on 190 Individuals with bipolar affective disorder. We examined the levels of inflammatory parameters, clinical stagind parameters and illness course. In female patients, there was a positive correlation between levels of hsCRP and IL-6 and the number of illness episodes. Levels of hsCRP and IL-6 were positively correlated with current manic symptoms as measured using YMRS. Abstract: Objectives: Immunological/inflammatory processes have been proposed to play an important role in the pathophysiology of mood disorders, including bipolar disorder (BD). The present study aimed to examine the influence of immune activation, measured on the basis of inflammatory markers, on the course of illness, proxied by the number of affective episodes, in patients with BD. Methods: We investigated the relationship between high-sensitive CRP (hsCRP) and Interleukin 6 (IL-6), two inflammatory markers and characteristics of course of illness (e.g. number of affective episodes, depressive and manic symptoms) amongst a group of 190 individuals with BD. Results: Among females with BD, there was a positive correlation between levels of hsCRP and the number of manic and depressive episodes. Moreover, levels of hsCRP and IL-6 were positively correlated with current manic symptoms, as measured by Young-Mania-Rating-Scale. There were no significant correlations between levels of the foregoing inflammatory markers, and manic and depressive symptoms in male individuals with BD. Furthermore, compared to their untreated counterparts, female patients treated with lithium demonstrated higher levels of hsCRP and male patients treated with atypical antipsychotics lower levels of hsCRP, respectively. Conclusions: Our results are suggesting that the association between inflammatory state and affective response in patients with BD may be gender-dependent. A future research would be to evaluate whether or not these gender differences can be observed in other inflammatory pathways associated with BD.